Perancangan Ulang Interior Rumah Sakit Jiwa Marzoeki Mahdi Bogor dengan Pendekatan Salutogenesis - Hana Aulia; Irma Damayantie (MAN 4 Kota Pekanbaru, 2026)
Mental health issues in Indonesia have become an increasingly critical public health concern, with approximately one in five individuals experiencing mental disorders. This study aims to redesign the interior of Marzoeki Mahdi Mental Hospital in Bogor using a salutogenic approach, focusing on health promotion and well-being rather than illness-centered treatment. Salutogenesis is based on the Sense of Coherence (SOC), consisting of comprehensibility, manageability, and meaningfulness as determinants of a supportive healing environment. This study applies a qualitative design method through field surveys, direct observation, and literature review, structured using the Rosemary Kilmer design process (analysis and synthesis stages). The redesign focuses on five functional spaces: registration area, doctor’s room, psychiatric consultation room, inpatient room, and group therapy room, with a minimum design area of 500 m². The proposed design optimizes natural lighting and ventilation, access to green open spaces, privacy management, ergonomic layouts, and calming materials and colors. The redesign creates a more humane, safe, and emotionally supportive environment, reducing stigma and fostering holistic recovery.